Gregg college keyboarding & document processing. - Ober, Scot; Johnson, Jack E.; Zimmerly, Arlene (Boston : McGraw-Hill, 2011)
This textbook presents an introduction to keyboarding. Keyboarding is the process of inputting data or text using a computer keyboard. Operating the keyboard by touch is an essential skill for many careers and a necessary skill useful for just about everyone. The intent of this text is to develop touch control of the keyboard and proper typing techniques, to build basic speed and accuracy, and to provide practice in applying those basic skills to the formatting of reports, letters, memos, tables, and other kinds of personal and business communications.
Includes index.
Keywords: Word processing -- Problems, exercises, etc; Keyboarding -- Problems, exercises, etc; Commercial correspondence -- Problems, exercises, etc; Report writing -- Problems, exercises, etc